HUBUNGAN TINGKAT PENDIDIKAN DAN PENGALAMAN TERKAIT STROKE DENGAN PENGETAHUAN STROKE - Francisca Jessyca; Poppy Kristina Sasmita (Bahasa Indonesia, 2021)
Background: Stroke is a medical emergency caused by poor or blocked blood flow to the brain resulting in brain damage and death. In the efforts to lower the number of stroke related mortality and encourage a higher quality of public health, knowledge and understanding of the definition, risks, signs and symptoms, and complication associated with stroke must become publicly available and further research should be encouraged. Higher education level and experience are expected to raise awareness of stroke disease. Objective: This study is conducted in order to determine the relationship between education level in correlation to knowledge of stroke at Paris Jaya in 2020. Method: The study is a descriptive analytic with a cross-sectional approach using 165 population of Poris Jaya. Population answered the provided questionnaire about sociodemographic and knowledge of stroke. The data collected was analyzed and scored using the Spearman test to see the correlation between educational level and knowledge while the Chi-square test was used to score the association between experience and knowledge. Result: There was a correlation between education level and knowledge score (p<0,05). There was also association between experience having stroke (p=0,01) and experience taking care stroke patient (p=0,03) with knowledge score. The most common education level that respondents have is graduated from senior high school. The average score of knowledge based on questionnaire was 68,667. Internet mostly used to find further information about this disease. Conclusion: Strong relationship are shown between education level and experience with knowledge of stroke at Poris Jaya in 2020